Step-by-step explanation:
-3x - 4 < 2
-3x < 2 + 4
-3x < 6
x < 6/ - 3
x < - 2
Answer:
perimeter= 12units
Step-by-step explanation:
steps are in picture
D. negative 67 because laplace’s expansion
Replace the x in x^2 + 5x - 1 by x+3:-
g(x) =
(x+3)^2 + 5(x+3) - 1
= x^2 + 6x + 9 + 5x + 15 - 1
= x^2 + 11x + 23
- thats g(x)
Are you trying to solve for x and y?
y=2x+1; x+2y=17
sub in one variable in the other equation.
x+2(2x+1)=17
x+4x+2=17
5x=15
x=3
now that you have x value, plug into the original equation to find y and check with the other.
y=2(3)+1 = 7
x+2y=17 = 3 + 2(7) = 17 ; 17=17